Kefir: composition and evaluation of in situ antagonistic activity against Staphylococcus aureus and Escherichia coli. (Revista Ciência Agronômica, 2018)
The aim of this study was to investigate whether produced kefir meets the identity and quality standards forfermented milks, to check the possibility of assigning a nutrition declaration, and to evaluate the antagonistic activity of thefermented milk against Staphylococcus aureus and Escherichia coli. Two different formulations of kefir (Kefir 1 and Kefir2) were prepared to determine the percentage composition, minerals, pH, total lactic acid bacteria, and antagonistic activityagainst Staphylococcus aureus and Escherichia coli. The results of the physicochemical evaluation indicated a statisticallysignificant difference between the formulations, except for the percentage of lipids, Ca, K, Mg and Na. The formulations metthe parameters of identity and quality in the fermented milks under evaluation. Possible nutrition declarations for Kefir 1 are‘source of proteins’ and ‘reduced calorie’, and for Kefir 2, ‘high protein content’ and ‘high zinc content’. The fermented milksshowed significant antagonistic activity against the tested microorganisms (> 24 h), with no activity seen after this period.Further studies involving kefir are suggested, exploring its potential as a probiotic food, and its inclusion in the diet of thepopulation.